Adenovírus em amostras fecais e do trato respiratório de crianças atendidas em um hospital de Goiânia, Goiás - Paz , Thainara Calixto da (2016)
Human adenoviruses (HAdVs) may cause several clinical syndromes, and are a major cause of respiratory and acute gastroenteritis (AGE), especially among children. However, data on viral load, in more than one type clinical sample obtained from the same child, are still scarce. The aims of the present study were to evaluate the frequency of the HAdV, to determine the load viral in clinical samples, and to proceed molecular characterization of positive samples from children up to five years of age in association with symptomatology. For this, 200 children attended at Hospital Materno Infantil in Goiânia, Goiás; between March 2014 ad July 2015. One fecal and one nasopharyngeal swab sample was obtained from each child. The clinical samples (fecal and nasopharyngeal swabs) were submitted the DNA extraction by a commercial kit (Qiagen-Hilden, Alemanha), and screened by RT-qPCR (TaqMan) assay, with specific primers and probe targeting the hexon region of HAdV genome. The global frequency of HAdVs was 21% (42/200). Positivity in swabs was 9.5% (19/200), and in fecal samples 16% (32/200). Among the symptomatic children (n=129), 21% were positive in fecal samples (22/105) and 9.2% (10/108) in swab samples. Futhermore, 4.5% (9/200) were positive in both clinical samples. High viral loads were observed in both fecal and nasopharyngeal swab samples from symptomatic and asymptomatic children, and major positivity was found in symptomatic children with high load viral. High viral loads were observed in samples from symptomatic and asymptomatic children. Major positivity and load viral was found betwenn symptomatic children. HAdV types 3 of species B and 41 of HadV F species were detected. We hope that the data obtained can help in a better understanding of the pathogenesis of HAdV in children.